Meta-analysis of anti-Saccharomyces cerevisiae antibodies as diagnostic markers of Behçet's disease with gastrointestinal involvement. Issue 10 (6th October 2020) - Cheng, Linlin; Li, Liubing; Liu, Chenxi; Yan, Songxin; Li, Yongzhe
Abstract : Objective: Due to common exposure to yeast in the alcoholic and baking industry, positive rate of anti- Saccharomyces cerevisiae antibodies (ASCA) is reportedly high in patients with Behçet's disease (BD) who have gastrointestinal symptoms (gastrointestinal BD (GIBD)). We performed a meta-analysis to assess the diagnostic value of ASCA in differentiating patients with BD from those with other chronic inflammatory bowel diseases. Methods: The meta-analysis is presented with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and Meta-analysis of Observational Studies in Epidemiology checklist. Relevant studies that investigated ASCA levels in patients with BD were retrieved from PubMed, EMBASE, Web of Science, SCOPUS and the Cochrane Library on 12 July 2019; the search was rerun on 12 February 2020. Stata/SE V.12.0 and Meta-DiSc V.1.4 were used to perform the meta-analysis and sensitivity analysis, disaggregated by isotypes of ASCA. Results: Nine studies were included in the meta-analysis. The results revealed a strong association between ASCA and GIBD, especially ASCA-IgG (OR=5.50 (95% CI 2.58 to 11.55), p=0.000) and ASCA-IgG+IgA (OR=5.36 (95% CI 1.40 to 20.45), p=0.014). The positivity rate of ASCA in GIBD was significantly higher than that in ulcerative colitis (UC): IgA (OR=2.13 (95% CI 1.30 to 3.50), p=0.003); IgG+IgA (OR=2.19 (95% CI 1.03 to 4.66), p=0.042); IgG/IgA ((=2.03 (95% CI 1.30 to 3.17), p=0.002). However, the frequency of ASCA-IgG was significantly higher in patients with Crohn's disease than GIBD (OR=0.48 (95% CI 0.28 to 0.83), p=0.009). There was no significant difference in ASCA positivity between BD without gastrointestinal involvement and healthy controls and between GIBD and intestinal tuberculosis (iTB) (p>0.05). Conclusion: ASCA may play a role in the pathogenesis of gastrointestinal involvement. Negative result of IgG favours the diagnosis of GIBD/BD when differentiated from Crohn's disease. ASCA-IgA showed moderate diagnostic performance in distinguishing GIBD and UC and the diagnostic performance was better in combination with IgG. However, ASCA may not be a useful serologic marker distinguishing GIBD and iTB. PROSPERO registration number: CRD42020115245.